SURABAYA ADOLESCENT'S PERCEPTION OF WOMEN'S SENSUALITY IN THE SHOWING “SHOWING IN THE SWIMMING POOL!! BILYY CAN’T STAND” - YOUTUBE CRAZY NIKMIR REAL - Syarizal Agam Mahendra; Heidy Arviani (Universitas Islam Balitar, 2021)
With so many YouTube channels and videos in Indonesia, there is competition. In addition, YouTube videos in Indonesia are also often found in the form of shows that violate the policies that have been made by Youtube. Like several video uploads on Nikita Mirzani's Youtube channel which eventually sparked controversy. One of them is titled “Buka-Bukaan di Kolam Renang!! Billy Gak Kuat” which has 15 million views and 198,000 likes and 25,000 dislikes. This video contains shows full of scenes of female sensuality. The purpose of this study was to determine the Surabaya youth's perception of female sensuality in the show